Konsep Kompetensi Guru menurut Imam Al-Ghazali - Dahyan, Dahyan; Koswara, S (Jurnal Penelitian Pendidikan Islam, 2016)
According to Al-Ghazali, a teacher must have a personal, pedagogical, and social competence. Personal competencies that must be owned by teachers include compassion to students and treat them as his own; emulate the Prophet so do not demand wages, rewards and awards, knowledge and contrary to his actions not his words. Pedagogical competence consists of not giving the title or dignity to the learner before he was worthy to carry it; learners reprimanded of despicable character; presenting lessons to students according to their level of functioning. As for social competence is not vilify another field of study.